ANALISIS PERHITUNGAN PAJAK PENGHASILAN (PPH) PASAL 21 BERDASARKAN PERATURAN DIREKTUR JENDRAL PAJAK NOMOR PER-31/PJ/2012 PADA PT. GELAEL INDOTIM MAKASSAR - Hj. Rostiaty Yunus (AkMen JURNAL ILMIAH, 2016)
This study aims to determine the application of Article 21 of the Income Tax made by PT. Gelael INDOTIM Makassar. The method used in this research is a comparative descriptive method is a method to perform a comparison between the theoretical framework based DGT Regulation No. Per-31 / PJ / 2012 on Income Tax (VAT) of Article 21 with facts on the ground. The results of this research is the mechanism of income tax (VAT) of Article 21 according to the DGT Regulation No. Per-31 / PJ / 2012 and procedures for calculation of Income Tax (VAT) of Article 21 carried out by PT. Gelael INDOTIM Makassar then comparing not found perbedaan.Perhitungan Tax Article 21 payable by DGT Regulation No. Per-31 / PJ / 2012 obtained yield was Rp.6.320.255, - While the data obtained from PT.Gelael INDOTIM Makassar based payroll obtained the same number of Rp.6.320.255.-